Is symptom-oriented follow-up still up to date? - Mundhenke, Christoph; Moebus, Volker (Breast Care, 2013)
The main objective of following patients after the primary treatment of breast cancer is the detection of potentially curable events, particularly the detection of local recurrences and contralateral breast cancer. Additionally, medical counseling on therapies, psychosocial aspects, side effects of therapies, and lifestyle interventions is important to improve the quality of life. There is an ongoing discussion about whether early detection of asymptomatic metastasis could improve the course of disease. Today, the follow-up is still symptom-orientated. Intensified imaging and laboratory check-ups have not been beneficial for the patients' survival. A follow-up in the first 2-3 years is recommended every 3 months. Because of the decreasing incidence of recurrence from year 4, 6-monthly screening intervals are recommended. The screening should include a history, physical examination, and a consultation. Routine diagnostic imaging - except for mammography/ultrasound - is not indicated in asymptomatic patients. Innovative therapies for patients with metastatic breast cancer have been introduced. Therefore, measures of an intensified follow-up could change in the future as novel endocrine combination or targeted therapies in molecular subtypes could significantly improve the survival in early detected metastasis. In the future, more individualized follow-up programs are conceivable. However, this idea is so far not supported by the available data. © 2013 S. Karger GmbH, Freiburg.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Breast cancer follow-up; Breast cancer subtypes; Imaging; Laboratory check-up; Lead time